The assemblages of transparent heavy minerals in Quaternary sediments of the Kielce-Łagów Valley (Holy Cross Mountains, Poland) - Ludwikowska-Kędzia, Małgorzata (Wydawnictwo Naukowe UAM, 2013)
The composition of the transparent heavy-mineral assemblages (0.25–0.1 mm) in Quaternary slope, karst, glacial, fluvio-glacial and fluvial deposits with different parent material was investigated in the Kielce-Łagów Valley (the central part of the Palaeozoic core of the Holy Cross Mountains). For the purpose, 93 samples of mostly sandy sediments were examined. Some marker and some supporting minerals can be distinguished. Slope and karst deposits are dominated by the abrasion-resistant minerals zircon, tourmaline, staurolite and rutile. This assemblage points at a source consisting of strongly weathered pre-Quaternary bedrock. Glacial and fluvioglacial deposits are dominated by medium-resistant and non-resistant minerals (garnet, amphibole, pyroxene and biotite). The two types of parent material of the heavy minerals are typical of the Quaternary deposits in the Polish uplands. The two sources are most clear in the younger (Vi-stulian and Holocene), mostly fluvial sediments. The results of the analysis imply that the impact of Pleistocene glaciers on the central part of the Holy Cross Mountains was neither large enough to hide the local mineralogical background, nor sufficient to dominate over the main processes transforming the mineral composition under the variable climatic conditions of the Quaternary, including aeolian processes and chemical weathering.
Keywords: Heavy-mineral analysis; Quaternary deposits; Holy Cross Mountains